Efficacy of biologics in the treatment of moderate‐to‐severe plaque psoriasis: a systematic review and meta‐analysis of randomized controlled trials with different time points. (19th August 2013) - Puig, L.; López, A.; Vilarrasa, E.; García, I.
Abstract Background Differences in response rates of biologics for the treatment of moderate‐to‐severe plaque psoriasis have been reported in several meta‐analyses published to date. However, the usefulness of these meta‐analyses is limited as they do not reflect currently approved recommendations in the Summaries of Product Characteristics (SmPCs) and clinical practice. Objective To estimate the efficacy of biologics in the treatment of moderate‐to‐severe plaque psoriasis in the currently approved conditions of use in the European Union (EU) at relevant time points for evaluation of response in clinical practice (failure assessment as recommended in the SmPCs and/or at the end of the induction phase). Methods Randomized placebo‐controlled studies of biologics currently authorized in the EU in adult patients with a diagnosis of moderate‐to‐severe plaque psoriasis were searched in several databases. A meta‐analysis using fixed or random‐effects model depending on heterogeneity across and within studies was performed. The efficacy was estimated using risk difference (RD) of Psoriasis Area and Severity Index (PASI) 50, PASI 75 and PASI 90 response rates at the endpoint in clinical trials, at the end of the induction phase (week 24) and at the time points recommended for evaluation of primary failure in the approved SmPCs. Several sensitivity analyses were performed to assess for robustness. Results Sixteen publications met the defined inclusion criteria. According to this meta‐analysis at the primary endpoint times, infliximab (at week 10) has the greatest probability of response with respect to placebo for all PASI‐based efficacy measures (PASI 50, PASI 75 and PASI 90). At the end of the induction phase (week 24), ustekinumab 45 mg has the greatest probability of achieving PASI 75 response (RD 75.5%, 95%CI 71.5–79.4%], followed by ustekinumab 90 mg, infliximab, adalimumab and etanercept. At the time points recommended for primary failure assessment according to the approved SmPCs, ustekinumab 45 mg (at week 28) also has the greatest probability of achieving PASI 50 response [RD 80.7%, 95%CI 77.2–84.2%], followed by ustekinumab 90 mg, infliximab, adalimumab and etanercept. Conclusion From a clinical practice perspective, and in terms of the most relevant efficacy measures (PASI 50 and PASI 75) and time points (end of induction phase [week 24] and time to assess primary failure as per the SmPCs), in the currently approved conditions of use ustekinumab is the most efficacious therapeutic alternative for moderate‐to‐severe plaque psoriasis, followed by infliximab, adalimumab and etanercept.